A hybrid piezoelectric and triboelectric nanogenerator with lead-free BZT–BCT/PDMS composite and PVA film for scavenging mechanical energy. Issue 12 (9th March 2023) - Gopal, S. R.; Velayutham, T. S.; Gan, W. C.; Cheong, J. Y.; Soh, A. E.
Abstract : A hybrid piezo/triboelectric nanogenerator (H/P-TENG) is designed for mechanical energy harvesting using polymer ceramic composite films; polydimethylsiloxane/Ba(Zr0.2 Ti0.8 )O3 –0.5(Ba0.7 Ca0.3 )TiO3 (PDMS/BZT–BCT) and polyvinyl alcohol (PVA). Abstract : A hybrid piezo/triboelectric nanogenerator (H/P-TENG) is designed for mechanical energy harvesting using polymer ceramic composite films; polydimethylsiloxane/Ba(Zr0.2 Ti0.8 )O3 –0.5(Ba0.7 Ca0.3 )TiO3 (PDMS/BZT–BCT) and polyvinyl alcohol (PVA). A lead-free BZT–BCT piezoelectric ceramic was prepared via solid-state method and blended into PDMS to form a series of polymer-ceramic composite films, ranging from 5% to 30% by weight. The films were forward/reverse poled with corona poling and their electrical properties were compared to non-poled samples. The H/P-TENG constructed with forward-poled 15 wt% BZT–BCT in PDMS achieved the highest open-circuit voltage, V oc of 127 V, short-circuit current density, J sc of 67 mA m −2, short-circuit charge density, Q sc of 118 μC m −2, and peak power density of 7.5 W m −2, an increase of 190% over pristine PDMS-based TENG. It was discovered that incorporating BZT–BCT into the PDMS matrix improved the triboelectric properties of PDMS. The overlapping electron cloud (OEC) model was used to explain the enhancement and the effect of poling direction of the PDMS/BZT–BCT composite used in H/P-TENG, providing fundamental knowledge of the influence of piezoelectric polarisation on contact electrification.